PENGARUH PROFITABILITAS, FIRM SIZE, GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN PADA INDUSTRI PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BEI PERIODE 2015-2019 - Joshua Victor Rusyanto; Paulina Van Rate; Victoria N. Untu (Universitas Sam Ratulangi, 2022)
The purpose of this study is to determine whether Profitability, Firm Size and Growth Opportunity have an influence on the Company Value of coal for the 2015-2019 period. The sample in this study were 14 coal companies listed on the Indonesia Stock Exchange in 2015-2019. This is a quantitative study and the analytical method used in this study is multiple linear regression analysis. With the results, profitability as measured by Return on Equity (ROE) and Firm Size has a significant effect on firm value as measured by Price to Book Value (PBV) in the research sample. Meanwhile, Growth Opportunity which is calculated by Price Earn Ratio (PER) does not have a significant effect on the value of the company in the sample, namely coal companies listed on the Indonesia Stock Exchange for the 2015-2019 period.